1H-NMR study of the interaction of daunomycin with B-DNA helices of methylated oligodeoxynucleotides. - Tran-Dinh, S (1984)
The interaction of daunomycin with B-DNA double helices of several methylated deoxynucleotides, d(C-G-m5C-G), d(m5C-G-C-G), d(C-G-m5C-G-C-G) and d(m5C-G-C-G-m5C-G) in solution was investigated by 1H-NMR spectroscopy at 500 MHz. At low temperature (t less than 20 degrees C for the tetramer and t less than 40 degrees C for the hexamers), several daunomycin-DNA complexes were observed in slow exchange with the drug-free DNA duplexes. The presence of daunomycin in a self-complementary double helix cancels the conformational symmetry of the two strands; the proton signals can split into several others owing to the difference between free and intercalated duplexes and to the many possible intercalation sites in a duplex (three for a tetramer, five for an hexamer). A model relating the chemical shifts of splitted proton signals to the various intercalated duplex conformations was given. The results show that one daunomycin molecule is associated with one duplex and that it can enter any intercalation site with equal probability; no side-effects were observed even for very short helices (of a tetramer). In the case of d(C-G-m5C-G) the association constant and the dissociation and association rates of the intercalated complex were evaluated.